Outcome of very-low-birth-weight babies managed with nasal continuous positive airway pressure, with or without surfactant, in a high-care nursery - Thokozile Cora Bopape-Chinyanga; Reenu Thomas; Sithembiso Velaphi (South African Medical Association, 2017)
Background. Very-low-birth-weight (VLBW) infants who require nasal continuous positive airway pressure (NCPAP) are managed in neonatal intensive care units (NICUs) in developed countries, while in low-resource settings this is not always possible. The failure rate of NCPAP provided outside NICUs is not well known. Objectives. To determine the failure rate, assessed as the need for invasive medical ventilation (iMV) and mortality on NCPAP in VLBW infants managed in a high-care nursery (HCN) within the first 72 hours of life. Methods. Records of VLBW infants managed with NCPAP, at Chris Hani Baragwanath Hospital, were reviewed for infant characteristics, need for iMV and mortality on NCPAP. Clinical risk index for babies (CRIB) was calculated for each infant. Comparisons were made between those who needed iMV and those who did not, and between survivors and non-survivors on NCPAP. Results. A total of 325 VLBW infants were managed with NCPAP in the HCN. Mean (standard deviation) birth weight was 1 120 (184)g, 98.5% were of gestational age (GA) <34 weeks and 14.9% were small for GA (SGA). Thirteen percent died while on NCPAP and 33% of survivors required iMV - an overall failure rate of 43%. Factors associated with iMV were high CRIB score (p<0.001), lower Apgar score (p=0.013), lower PaO2 (p=0.022) and high base deficit (p=0.034). Those who died were more likely to have extremely low birth weight (p<0.001), lower GA (p<0.001), high CRIB score (p<0.001) and base deficit (p<0.001). On multivariate analysis, the predictors for need of iMV were low Apgar score (p=0.033), SGA (p=0.042) and CRIB score (p=0.005), while that of mortality on NCPAP was birth weight. Conclusion. Although failure rate of NCPAP in VLBW infants managed in HCN is high, a significant proportion of VLBW infants benefit from this intervention.